2013
DOI: 10.1364/ao.52.002116
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of basal cell carcinoma using dynamic focus optical coherence tomography

Abstract: Optical coherence tomography (OCT) is becoming a popular modality for skin tumor diagnosis and assessment of tumor size and margin status. We conducted a number of imaging experiments on periocular basal cell carcinoma (BCC) specimens using an OCT configuration. This configuration employs a dynamic focus (DF) procedure where the coherence gate moves synchronously with the peak of the confocal gate, which ensures better signal strength and preservation of transversal resolution from all depths. A DF-OCT configu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…The system operates at 1300 nm and uses a super luminescent diode (SLD) with a 3 dB spectral bandwidth of 54 nm. The dynamic focus allows better penetration, as demonstrated in previous studies of basal cell carcinoma [8]. DF-OCT removes the need for deconvolution of axial reflectivity profiles with the confocal gate profile [9], [10].…”
Section: Dynamic Focus Oct Configurationmentioning
confidence: 80%
“…The system operates at 1300 nm and uses a super luminescent diode (SLD) with a 3 dB spectral bandwidth of 54 nm. The dynamic focus allows better penetration, as demonstrated in previous studies of basal cell carcinoma [8]. DF-OCT removes the need for deconvolution of axial reflectivity profiles with the confocal gate profile [9], [10].…”
Section: Dynamic Focus Oct Configurationmentioning
confidence: 80%
“…The cross‐sectional images are dependent on the backscattering properties of the skin . The intrinsic scattering characteristic is proportional to the density, size, and shape of the cells . It is worth mentioning that we introduced dynamic focus OCT, in which there is no need to decorrelate the effect of confocal gate and sensitivity drop‐off since the peak of the confocal and coherence gates move simultaneously.…”
Section: Methodsmentioning
confidence: 99%
“…Optical coherent tomography imaging has become a powerful tool in skin diagnostics in recent years. We have also studied on enhancing these images to improve the morphological information in OCT images of skin . However, there is a lack of information available on what a clinician should see in healthy skin on OCT imaging.…”
Section: Introductionmentioning
confidence: 99%
“…14,15,24 However, the penetration depth of RCM imaging is limited to 100 to 200 μm, which is not sufficient for estimating the deeper margins of BCCs. Therefore, OCT imaging, which has been proven to visualize the microanatomy of BCCs to depths of at least 1 mm, [40][41][42][43][44][45] is a complementary technology that can be used for this purpose. Superficial and nodular BCCs are particularly well-imaged with OCT. A number of observational studies have reported the ability of OCT to reliably detect the depth of BCCs.…”
Section: Introductionmentioning
confidence: 99%
“…Superficial and nodular BCCs are particularly well-imaged with OCT. A number of observational studies have reported the ability of OCT to reliably detect the depth of BCCs. [41][42][43][44][45] Depth measurements with OCT are more accurate, due to its higher resolution, than those with other approaches such as ultrasound and magnetic resonance-microscopy. In addition, both OCT and RCM are optical imaging modalities, which more easily facilitates their integration into a single instrument.…”
Section: Introductionmentioning
confidence: 99%